Actualising the Value of Mataram Cultural Tourism as Local Wisdom To Build Generation Z Identity - Latif , B Syarifuddin; Demolingo , Ramang H; Pallawagau, Andi; Raflikeza, Muhammad Firdaus (CV ODIS, 2024)
The archipelago's culture is a heritage that must be maintained and preserved. Culture includes all behaviors and customs that have been going on for generations and are rooted and inherited by the community. As a great nation, Indonesia has a rich culture owned by every tribe, and it is spread from Sabang to Merauke. The development of technology and the rapid flow of globalization are challenges for a nation in its cultural preservation efforts. Unstoppable access to information and communication makes cultural shifts in a nation easy. The young generation is the most vulnerable generation to experience cultural shifts. As Generation Z, supported by the development of information and communication technology, the function of communication tools and information media is not only used as a supporting tool but has become necessary. Information media, such as social media, is also growing, making the younger generation an active user and access to information can move quickly. This fact, the Indonesian nation will also be affected by globalization, and local wisdom is increasingly weakening among the current generation Z regarding social life. Therefore, efforts are needed to increase the knowledge and interest of the younger generation in their nation's culture. This article discusses activities related to cultural tourism and focuses on the form of narratives that can be used in culture-based tourism activities. The narrative aims to attract Generation Z to promote tourism. Generation Z is a generation that developed or grew up amid exposure to the internet, social media, and technology. By tracing newspapers, especially in social media, both from the colonial and contemporary periods, and conducting interviews with several sources, it was found that tourism activities by the community were related to the culture that had existed during the colonial period. Meanwhile, the narrative that can attract Generation Z is an alternative narrative that is interesting, not monotonous, and has an attachment to locality. This research uses descriptive qualitative data analysis techniques through interviews with informants, observation, and documentation.